2016
DOI: 10.1590/s1413-65382216000100005
|View full text |Cite
|
Sign up to set email alerts
|

Dificuldades e Sucessos de Professores de Educação Física em Relação à Inclusão Escolar

Abstract: RESUMO: objetivou-se identificar as situações de dificuldade e as situações de sucesso de dois professores de Educação Física, em turmas regulares em que há alunos com deficiência e alunos com autismo matriculados, para subsidiar o planejamento de uma formação continuada. Os participantes foram dois professores de Educação Física que atuavam em Escola Municipal de Ensino Fundamental, do 1° ao 5° ano, de uma cidade da região Centro-Oeste do Estado de São Paulo. Realizaram-se filmagens de 12 aulas de P1 e 16 aul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 10 publications
0
3
0
15
Order By: Relevance
“…We suspect that curricular implementation and adaptations within the actual PE class are likely made on site, case-by-case, or are improvised. Some studies have found that, after PE teachers undergo training workshops and lectures administered by specialized leaders in the fi eld, or if they have previous experience with inclusion, they express a sense of improved confi dence and positive dispositions toward teaching students with disability with diverse backgrounds 43,44 . However, Haegele et al 45 suggested that Brazilian physical educators' full support of inclusion relies on their development in specialized training, although they stated that they would accept teaching students with disabilities in their classes.…”
Section: The Right To Full Access To Education: the Case Of Inclusive Pementioning
confidence: 99%
“…We suspect that curricular implementation and adaptations within the actual PE class are likely made on site, case-by-case, or are improvised. Some studies have found that, after PE teachers undergo training workshops and lectures administered by specialized leaders in the fi eld, or if they have previous experience with inclusion, they express a sense of improved confi dence and positive dispositions toward teaching students with disability with diverse backgrounds 43,44 . However, Haegele et al 45 suggested that Brazilian physical educators' full support of inclusion relies on their development in specialized training, although they stated that they would accept teaching students with disabilities in their classes.…”
Section: The Right To Full Access To Education: the Case Of Inclusive Pementioning
confidence: 99%
“…Não houve uma graduação do quanto os facilitadores representaram individualmente a sua importância, mas na presença dos entrevistados a confiança no espaço da prática, a segurança e o conhecimento preparo do profissional ficaram evidentes e com uma colocação de destaque pelos entrevistados. Em um estudo onde se objetivou identificar as situações de dificuldade e as situações de sucesso de dois professores de EF em turmas com alunos deficientes físicos e alunos com autismo, os pesquisadores concluíram que encontraram dificuldades para incluir os alunos com autismo, mas eles também vivenciaram situações de sucesso (FIORINI; MANZINI, 2016). O estudo permitiu um detalhamento das necessidades dos professores e o entendimento de que a formação continuada deveria ser desenvolvida no sentido de, considerar o contexto das aulas, auxiliar na minimização das dificuldades e valorizar as ações de sucesso.…”
Section: Discussõesunclassified
“…No entanto, ainda é frequente a queixa referente ao despreparo dos professores de Educação Física para atuar na perspectiva inclusiva (AGUIAR;DUARTE, 2005;FALKENBACK et al, 2007;GORGATTI;DE ROSE JR., 2009;COSTA, 2010;FERREIRA et al, 2013;ROSSI;MUNSTER, 2013;FIORINI;MANZINI, 2016). O sentimento de frustração decorrente do insucesso nas tentativas de incluir os estudantes com deficiências nas práticas pedagógicas de Educação Física é relatado pelos professores, os quais responsabilizam, entre outras dificuldades, as poucas oportunidades de experiências práticas durante o processo de formação inicial (FIORINI; MANZINI, 2012; ROSSI; MUNSTER, 2013).…”
Section: Formação Dos Profissionais De Educação Física Para Atuar Jununclassified